2023
DOI: 10.1186/s12916-023-03135-8
|View full text |Cite
|
Sign up to set email alerts
|

Associations between types and sources of dietary carbohydrates and liver fat: a UK Biobank study

Josefina Orliacq,
Aurora Pérez-Cornago,
Siôn A Parry
et al.

Abstract: Background and aims Excess energy intake can lead to metabolic dysfunction-associated steatotic liver disease (MASLD), but the relationship between dietary carbohydrate intake and liver fat content remains unclear. This study aimed to examine the associations between types and sources of dietary carbohydrates and liver fat content. Methods UK Biobank participants with no pre-existing diabetes, liver disease or cardiovascular disease reported dietar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Differing from those of previous research, our MR analyses did not reveal a causal relationship between 24 food intakes and NAFLD. Some cross-sectional and cohort studies have suggested a positive association between high-salt, high-sugar, high-fat, and high-cholesterol diets and an increased risk of NAFLD [30][31][32] . However, our MR analysis did not reveal a causal relationship between the frequency of adding salt to food, overall processed meat intake, never eat sugar vs. no sugar restrictions, and NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Differing from those of previous research, our MR analyses did not reveal a causal relationship between 24 food intakes and NAFLD. Some cross-sectional and cohort studies have suggested a positive association between high-salt, high-sugar, high-fat, and high-cholesterol diets and an increased risk of NAFLD [30][31][32] . However, our MR analysis did not reveal a causal relationship between the frequency of adding salt to food, overall processed meat intake, never eat sugar vs. no sugar restrictions, and NAFLD.…”
Section: Discussionmentioning
confidence: 99%